Decoloniality in the ELT: (mis)encounters between reading axis of the CCNC and of the CEFR - Cruz, Alciclei da Graça; Teixeira, Wagner Barros (The ESPecialist, 2025)
This paper is a clipping from Cruz’s master’s research (2024), developed in the Graduate Program in Languages at the Federal University of Amazonas, linked to the area of Applied Linguistics, from a critical and intercultural perspective. As a guiding question for this work, we propose the following question: in what ways does the Common European Framework of Reference for Languages (Conselho da Europa, 2001) impact/influence the curricular guidelines for English language teaching in Brazil and, in particular, in Amazonas? Starting from an analysis from a critical decolonial perspective (Quijano, 1992, 2000; Walsh; Oliveria; Candau, 2018), to answer the proposed question, we used bibliographic and documentary research to draw up a brief overview of the topic suggested in this article. The results show that the descriptors of the Reading Axis, for the English Language area, outlined by the Common Core National Curriculum (Brasil, 2018) are proposed in line with the proposals drawn up by the Common European Framework of Reference for Languages, which reveals the powerful influence of Eurocentric conceptions on language teaching in Brazil and, specifically, in Amazonas, the focus of this research. Thus, there is an urgent need to rethink the national curriculum guidelines and their regional developments, taking into account the specificities of each location and proposals that value decolonial epistemologies and perspectives.